2018
DOI: 10.2337/db18-0040
|View full text |Cite
|
Sign up to set email alerts
|

High CD8 T-Cell Receptor Clonality and Altered CDR3 Properties Are Associated With Elevated Isolevuglandins in Adipose Tissue During Diet-Induced Obesity

Abstract: Adipose tissue (AT) CD4 and CD8 T cells contribute to obesity-associated insulin resistance. Prior studies identified conserved T-cell receptor (TCR) chain families in obese AT, but the presence and clonal expansion of specific TCR sequences in obesity has not been assessed. We characterized AT and liver CD8 and CD4 TCR repertoires of mice fed a low-fat diet (LFD) and high-fat diet (HFD) using deep sequencing of the TCRβ chain to quantify clonal expansion, gene usage, and CDR3 sequence. In AT CD8 T cells, HFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 59 publications
(78 reference statements)
3
28
0
Order By: Relevance
“…Interestingly, among PLWH seen in a European metabolic diseases clinic with a range of fat alteration phenotypes, circulating CD8 + T cell activation was higher in both patients with lipoatrophy and in those with central fat accumulation than in patients without clinically apparent fat redistribution 124 . In addition, CD8 + T cells in SAT from PLWH without clinically apparent lipodystrophy have increased antigen receptor clonality 120 , a finding which is also reported in animal models of obesity 125 . This finding could reflect local T cell expansion, although some studies have reported a lack of Ki-67 (a marker of proliferating cells) expression and high CD57 (a marker of late differentiation or senescence and an indicator of reduced replicative capacity) expression on CD8 + cells from adipose tissue of SIV-infected macaques, which could reflect minimal in situ proliferation 87,126,127 .…”
Section: Role Of Adipose Immune Systemmentioning
confidence: 54%
“…Interestingly, among PLWH seen in a European metabolic diseases clinic with a range of fat alteration phenotypes, circulating CD8 + T cell activation was higher in both patients with lipoatrophy and in those with central fat accumulation than in patients without clinically apparent fat redistribution 124 . In addition, CD8 + T cells in SAT from PLWH without clinically apparent lipodystrophy have increased antigen receptor clonality 120 , a finding which is also reported in animal models of obesity 125 . This finding could reflect local T cell expansion, although some studies have reported a lack of Ki-67 (a marker of proliferating cells) expression and high CD57 (a marker of late differentiation or senescence and an indicator of reduced replicative capacity) expression on CD8 + cells from adipose tissue of SIV-infected macaques, which could reflect minimal in situ proliferation 87,126,127 .…”
Section: Role Of Adipose Immune Systemmentioning
confidence: 54%
“…14 Unexpectedly, the VAT of obese mice was found enriched with CD8 T cells with a clonal T cell receptor (TCR) repertoire, suggesting local expansion toward cognate antigens with a potential implication of antigen specificity in obesity. 15 T cells infiltrating the VAT have also been described in humans. Th1 and Tc1 cells were found increased, 16 while impaired T cell regulation was observed in the VAT of obese patients 14 when compared with subcutaneous adipose tissue (SAT) or with PB of the same patients.…”
Section: Obesity Studiesmentioning
confidence: 96%
“…CD8 + T cells appear to interact with adipocytes and macrophages in obese AT to trigger an inflammatory cascade via an interactive circle (57). A recent study raised the possibility that isolevuglandin-containing antigens presented by M2-polarized macrophages to CD8 + T cells in the AT of DIO mice may preferentially expand cognate TCR clonotypes (58). Thus, obesity-associated antigens may select and modify the TCR repertoire in the AT and thereby alter immune responses at adipose depots.…”
Section: Adipose Tissue Immune Cells In Obesity-associated Inflammationmentioning
confidence: 99%